Influence of rainfall on abundance of mites in coffee plants - abreu, Fernanda aparecida; Reis, Paulo Rebelles; Marafeli, Patricia de Padua; Silva, Rogério Antonio; Bernardi, Leopoldo Ferreira de Oliveira; Carvalho, César Freire (Coffee Science - ISSN 1984-3909, 2014)
The coffee plant Coffea spp. suffers pest attack, which according to climatic conditions present in the culture system can reduce fruit production. Rainfall is considered an important natural factor in the regulation of arthropods populations. The objective of this study was to evaluate the effects of rainfall during the seasons, on the occurrence of the main species of mites in coffee. The experiment was carried out at the EPAMIG farm in São Sebastião do Paraíso, MG, from January 2011 to June 2012. The useful area of the experiment was 8,820 m² with a total of 3,150 trees, and the useful part of the plot consisting of 2,100 plants, where were monthly collected at random 25 leaves from the middle third in 84 plants, totaling 2.100 leaves. Among the pest mites, the phytophagous mite Brevipalpus phoenicis (Geijskes, 1939 (Tenuipalpidae) was found in greater number on both dry and rainy seasons. The mite Oligonychus ilicis (McGregor, 1917) (Tetranychidae) was found at a higher incidence on the months of low rainfall. Rainfall also influences the occurrence of predatory mites belonging to the family Phytoseiidae, however, the species Euseius citrifolius Denmark & Muma, 1970 (Phytoseiidae), is found throughout the year.